The Influence of Quality of Work Life on the Professionalism of Traffic Directorate (Ditlantas) Personnel with Organizational Intelligence as a Moderating Variable - Harahap, Dio Arza Andamaris; Hardjo, Suryani; Patisina, Patisina (UNIVERSITAS PAKUAN, 2025)
As professional police personnel, this can be seen from their attitude of struggle, dedication, discipline, and responsibility in carrying out their duties.This study aims to examine the influence of quality of work life on the professionalism of the Traffic Police Personnel at the Medan City Police Resort, with organizational intelligence as a moderating variable.Professionalism in the police is the attitude, way of thinking, actions, and behavior of a police officer based on knowledge, particularly police ethics and police science, in providing the best service to achieve order, security, and the rule of law in society.This research uses a quantitative method with a sample size of 215 personnel.The data collection methods used are the quality of work life scale, professionalism scale, and organizational intelligence scale.The data analysis technique used in the research is Structural Equation Model (SEM).The results of this study indicate that there is no significant positive effect between quality of work life and professionalism with organization intelligence as a moderating variable among Ditlantas Polri personnel, based on a t-statistic value of 0.280 1.96 and a p-value of 0.780 0.05.The magnitude of the influence of quality of work life on professionalism with organization intelligence as a moderating variable is only 0.012 (1.2%), which is considered insignificant, where the significance value is 1.96 for the t-statistic and 0.05 for the p-value.